Standardized Sampling Plan for the Thrips Frankliniella schultzei (Thysanoptera: Thripidae) on Watermelon Crops - Pinto, Cleovan Barbosa; Sarmento, Renato Almeida; da Silva Galdino, Tarcísio Visintin; Pereira, Poliana Silvestre; Barbosa, Breno Gomes; Oliveira Lima, Carlos Henrique; da Silva, Nilson Rodrigues; Picanço, Marcelo Coutinho (Journal of economic entomology, 2017)
Sampling plans are essential components of integrated pest management programs. The thrips Frankliniella schultzei (Trybom) (Thysanoptera: Thripidae) is an important pest of watermelon crops. Despite the importance of sampling plans and of F. schultzei as a pest of watermelon crops, no research has been previously conducted on this subject for this crop. The objective of this work was to create a standardized sampling plan for F. schultzei in watermelon crops. Over two consecutive years, weekly samplings were performed in commercial watermelon crops. The aim of these assessments was to select the best sampling unit and the best sampling technique for F. schultzei assessment and to determine the number of samples necessary for a standardized sampling plan for this pest. In watermelon crops in the vegetative, flowering, and fruiting stages, the ideal location for sampling F. schultzei was the most apical leaf of the branches. The best sampling technique was a direct count of F. schultzei individuals. The F. schultzei sampling plan involved the evaluation of 69 samples per plot. The execution duration of this sampling plan in 1- to 15-ha plots was <1 h and was inexpensive (<US$ 2 per sampling). This has not been reported for watermelon before.